Evaluating The Reliability and Availability of A High-Pressure Die Casting System ‎Featuring Two Units and Cold Standby Redundancy - Kaur, Ms. Navpreet; Singh , Dr. Karanvir; Garg , Dr. Vanita (International Journal of Basic and Applied Sciences, 2025)
This study presents a behavioral and availability analysis of a high-pressure die casting plant ‎modelled as a two-unit system with cold standby redundancy. By investigating the effects of ‎varying repair rates (α) on system availability, we demonstrate that increased repair rates ‎correlate positively with availability, aligning with practical expectations in industrial ‎applications. Application of the regenerative graphical technique (based on the center of ‎pressure) allows for evaluating the parameters very quickly without involving the computation of ‎state equations or resultants. Our analysis highlights the potential inclusion of multi-unit ‎systems with perfect and imperfect switch-over devices to broaden the model’s applicability. ‎Additionally, insights are provided for conditions under which failure and repair rates may ‎vary, offering directions for future profit-and-loss analysis. We discuss how operational costs ‎can be minimized by leveraging expertise gained through repeated server visits, thereby ‎reducing the need for primary interventions. This study offers a flexible framework for ‎evaluating various system states and assessing key performance attributes, with implications ‎for cost-effective maintenance strategies in industrial settings‎.